LEAN CANVAS AS AN ANALYSIS TOOL FOR MSMES KITA ROBUSTA COFFEE IN KUNIRAN REGENCY NGAWI FOR BUSINESS DEVELOPMENT - Setyaningrum, Kharisma; Sardanto, Rino (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim: The purpose of this study is to examine how Lean Canvas can be used as a strategic tool to support the growth of Kita Robusta Coffee in Dk. Miridoyong, Rt. 03/Rw. 03, Ds. Kuniran, Kec. Sine, Kab. Ngawi, Prov. East Java. Design/Methods/Approach: The research used descriptive qualitative techniques to identify key issues faced by MSME, such as limited manufacturing capacity, poor marketing, and the need for innovative products and packaging. Direct observation, in-depth interviews, and document analysis were used to collect data. Research Finding:The results show that Lean Canvas is effective in identifying and formulating solutions to the core problems faced by this MSME. Through the application of Lean Canvas, Kita Robusta Coffee can better understand their business structure, identify market opportunities, and design more targeted marketing strategies. Theoretical contribution/Originality : This research expands the literature on the application of Lean Canvas in the context of traditional coffee MSMEs in Indonesia, which has not been widely discussed before. Practitionel/Policy implication : The results of this study provide strategic guidance for MSMEs to optimize production capacity, expand market reach through marketing digitalization, and increase product attractiveness through packaging innovation. Research limitation : This study only focuses on one small-scale MSME, so the results cannot be generalized to other sectors. In addition, this study only covers business model analysis without directly evaluating strategy implementation.